2015
DOI: 10.1111/aen.12187
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of Vespula germanica (Hymenoptera: Vespidae) wasps exposed to essential oils

Abstract: Secondary plant metabolites such as those present in essential oils can be toxic to herbivorous insects and also repel attack, given they play a role in selection and acceptance of host plants. However, few studies have dealt with the use of plant-based repellents to manage invasive wasps. The objective was to assess essential oils with potential as wasp repellents, and to gain further insight as to how they affect the learning capacities of these insects. Five essential oils were tested on Vespula germanica (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…After a single wasp landed, we removed it with a handheld insect aspirator (as in Buteler et al . ), in order not to record the same wasp twice.…”
Section: Methodsmentioning
confidence: 99%
“…After a single wasp landed, we removed it with a handheld insect aspirator (as in Buteler et al . ), in order not to record the same wasp twice.…”
Section: Methodsmentioning
confidence: 99%
“…In vespid wasps, volatile molecules can induce dramatically different responses depending on their concentration and the context in which they are sensed. For instance, the ability of tea tree oil and lemongrass oil to act as yellowjacket repellents is dose-dependent, with higher concentrations producing a stronger effect [25]. The ability of essential oils to repel also depends on their proximity to the attractant source, with repellency increasing when oils are placed closer to the attractant [26].…”
Section: Discussionmentioning
confidence: 99%
“…Available management tools are scarce including baited traps and toxic baits with fipronil (Hanna, Foote, & Kremen, ; Harris & Etheridge, ; Sackmann, Rabinovich, & Corley, ) which need to be used with caution due to its toxicity to the environment and non‐target organisms (Balança & del Visscher, ; Gunasekara & Troung, ). Recently, plant‐based repellents have been proposed as a potential alternative to classic pesticides against pest wasps, in certain scenarios (Boevé, Honraet, & Rossel, ; Buteler, Lozada, D'Adamo, Melo, & Stadler, ; Zhang, Schneidmiller, & Hoover, ). They reported the repellent effect of numerous essential oils as well as some of their synthetic constituents against yellowjackets and paper wasps (Boevé et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, wasp repellents have been studied in terms of the individual response of naïve wasps and captured in baited traps (Boevé et al, ; Zhang et al, ). More recently, Buteler et al () took into account the role of learning and memory mechanisms at the individual level, when analysing the repellent effect of essential oils on the relocation behaviour of V. germanica . These authors showed that the repellent effect decreases after previous experience with the food source, in the absence of the repellent odour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation